A new species of deep-water triplefin (Pisces: Tripterygiidae) in the genus Ruanoho from coastal New Zealand waters - Stewart, Andrew L.; Knudsen, Steen W.; Clements, Kendall D. (Zootaxa, 2021)
A new endemic species of triplefin Ruanoho scurra is described from deep water (108–216 m) on the shelf region around coastal New Zealand (Northland to Stewart Island). It is differentiated from its congeners by the combination of fresh colour (bright yellow spots on the head and anterior body, oblique lines on the dorsal and anal fins, and sub-vertical lines on the caudal) as well as some proportional measurements. Comments are made on the relationship with its congeners, and evolutionary history of the family in New Zealand waters, along with observations on the habitat in which this new species is found. This paper formally describes the species first mentioned in Stewart & Clements 2015:1523 as the polkadot triplefin.